The National Health Service - Great Britain. Central Office of Information. (London : His Majesty's Stationery Office, 1948)
1948 1948 1940s 38 pages authorised officers, they have the duty of putting persons who need care and treatment into touch with the facilities available in clinics or hospitals. They are also responsible for the care of those mental defectives who can be adequately looked after in the community. Furthermore, wide functions in relation to the after-care of mental patients are assigned to Local Health Authorities. Where special transport is necessary for the sick or injured (including the mentally afflicted and the victims of street accidents), or for mothers going to hospital for confinement, it is the duty of the Local Health Authority to provide it free. Each authority has to arrange a service of ambulances and cars to take anyone in its area who is unfit to travel by ordinary means to wherever it is necessary for him to go for medical care, nursing or dental treatment ; and to take any such patient who has been receiving treatment in its area home again, wherever he may live. Provided special transport is necessary for medical reasons, the service can be used without payment by people who are not using the public medical service but have made private arrangements for treatment. Mothers and Children The remaining duties of the major local authorities are nearly all concerned with the welfare of mothers and children. As health authorities they have a general duty to 'make arrangements for the care, including in particular dental care', of expectant and nursing mothers and of children under five not attending nursery schools. As education authorities they must hold regular medical and dental inspections of all children going to schools maintained by them (including 'voluntary' schools), and must see to it that 'comprehensive facilities for free medical treatment' are available for all schoolchildren. For some time to come these and other duties will be carried out mainly by the use of clinics where doctors, midwives, and health visitors can watch over the health of expectant mothers (antenatal care), make sure they are fit after childbirth (postnatal care), and follow the progress of their babies (infant welfare), supplying certain 'welfare foods' for mothers and children cheaply or without charge, and arranging for children to be immunised against diphtheria and vaccinated (no longer compulsorily) against smallpox. The family doctors will be brought into closer touch with this work, especially as health centres are built up, and with some of it the hospital service will co-operate. Under the Health Act, County and County Borough Councils may provide day nurseries (which are not nursery schools) for children below school age whose mothers cannot care for them properly during the day, for instance, because they have to go out to work. Councils may charge for 'articles provided', such as meals. 22 21/1489